2004
DOI: 10.1097/01.psy.0000106884.58744.09
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Affects Heart Rate Variability During Sleep

Abstract: Changes in heart rate variability associated with acute stress may represent one pathway to disturbed sleep. Stress-related changes in heart rate variability during sleep may also be important in association with chronic stressors, which are associated with significant morbidity and increased risk for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
204
4
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(237 citation statements)
references
References 49 publications
13
204
4
1
Order By: Relevance
“…One of the mechanisms might be a shift towards sympathovagal balance during NREM sleep (Hall et al, 2004). The lack of significant effects in sleep efficiency in the present study may imply that the perceived stress levels were not severe enough to give these kinds of effects.…”
Section: Work Stress and Sleepcontrasting
confidence: 41%
See 1 more Smart Citation
“…One of the mechanisms might be a shift towards sympathovagal balance during NREM sleep (Hall et al, 2004). The lack of significant effects in sleep efficiency in the present study may imply that the perceived stress levels were not severe enough to give these kinds of effects.…”
Section: Work Stress and Sleepcontrasting
confidence: 41%
“…Moreover, the present reduction of sleep length was relatively moderate and there was no accumulation of sleepiness over the week, which indicated that the subjects did not build up a sleep debt during the workweek. However, short sleep length has been shown to be a risk factor for ill health and mortality (Hall et al, 2004;Kripke et al, 2002). The mechanism leading to ill health might be through a suppression of many of the anabolic processes that take place during sleep, leading to an allostatic up regulation (Buckley & Schatzberg, 2005;McEwen, 2006).…”
Section: Work Stress and Sleepmentioning
confidence: 99%
“…In this way, we controlled for the effect that arousals and intervening wakefulness may have on HRV measures (27). Reduced parasympathetic modulation during sleep, as found in the women with PMS when symptomatic, may impact the restorative properties of sleep (28). Consequently, the perception of sleep quality may be affected; women with PMS report a poorer sleep quality, although polysomnographic-defined sleep efficiency is unchanged, when they are symptomatic in the late-luteal phase compared with the follicular phase (24).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have also examined psychosocial factors as predictors of ABP dipping (Ituarte, Kamarck, Thompson, & Bacanu, 1999;) under the assumption that nocturnal physiology may be altered by daytime behaviors and concerns (Hall et al, 2004). Overall, however, surprisingly little research, to date, has examined the extent to which daytime ABP or nocturnal changes in ABP may mediate the effects of psychosocial processes on CVD risk.…”
Section: Why Study Psychosocial Processes and Abp?mentioning
confidence: 99%